Implementasi Program Kartu Indonesia Pintar (KIP) Kuliah Merdeka dalam Mewujudkan Pemerataan Pendidikan Tinggi (Studi Kasus: Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana) - Putri, Ni Kadek Bella Akmilia; Wijaya, Komang Adi Sastra; Wirantari, I Dewa Ayu Putri (Socio-political Communication and Policy Review, 2025)
This study aims to determine the extent to which the implementation of this program is in realizing equitable higher education. This study applies a qualitative type with a descriptive approach. The analysis uses the Program Implementation theory from Charles O. Jones. The findings show that the implementation of the KIP Merdeka College Program is very significant in realizing equitable higher education at the Faculty of Social and Political Sciences, Udayana University. However, there are several obstacles in the interpretation dimension such as lack of socialization, for example socialization related to the technical and procedures for filling in monitoring and evaluation which results in many students experiencing errors and confusion. In addition, there is minimal socialization regarding the accountability of the use of living expenses to students receiving the KIP Kuliah Merdeka program, as well as limited transparency of information regarding the time of disbursement of funds and the technical amount of living expenses assistance. However, in terms of organization and application, the implementation of this program is running optimally. In terms of organization, there is a clear organizational structure and implementation of tasks. Meanwhile, in the application, the results obtained showed that this program was positively accepted by students and could provide assistance in the form of open access and opportunities to pursue higher education, up to the beginning of equalizing higher education. Abstrak Penelitian ini bertujuan untuk mengetahui sejauh mana implementasi program ini dalam mewujudkan pemerataan pendidikan tinggi. Penelitian ini menerapkan tipe kualitatif dengan pendekatan deskriptif. Analisis menggunakan teori Implementasi Program dari Charles O. Jones. Hasil temuan menunjukkan bahwa implementasi Program KIP Kuliah Merdeka sangat signifikan dalam mewujudkan pemerataan pendidikan tinggi di Fisip Universitas Udayana. Namun terdapat beberapa kendala dalam dimensi interpretasi seperti kurangnya sosialisasi, misalnya sosialisasi terkait teknis dan prosedur pengisian, monitoring dan evaluasi yang mengakibatkan banyak siswa mengalami kesalahan dan kebingungan. Selain itu, minimnya sosialisasi mengenai pertanggungjawaban penggunaan biaya hidup kepada mahasiswa penerima program KIP Kuliah Merdeka, serta keterbatasan keterbukaan informasi waktu terkait pencairan dana dan teknis besaran bantuan biaya hidup. Meskipun demikian dari segi organisasi dan aplikasi, implementasi program ini berjalan optimal. Dari segi organisasi terdapat susunan organisasi dan pelaksanaan tugas yang jelas. Sedangkan dalam aplikasi diperoleh hasil bahwa program ini mampu diterima secara positif oleh siswa dan dapat memberikan bantuan berupa keterbukaan akses dan kesempatan untuk menempuh pendidikan tinggi, hingga permulaan pemerataan pendidikan tinggi. Kata Kunci: Implementasi Program, KIP Kuliah Merdeka, Pemerataan Pendidikan Tinggi, Fisip Universitas Udayana